Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide